2000
DOI: 10.7773/cm.v26i3.597
|View full text |Cite
|
Sign up to set email alerts
|

Water temperatures in the Gulf of California in May and June 1996 and their relation to the capture of giant squid (Dosidicus gigas D’Orbigny, 1835)

Abstract: Recibido en diciembre de 1998; aceptado en mayo de 2000 RESUMEN Se analizó la relación entre la temperatura del agua y las capturas de calamar gigante en el Golfo deCalifornia. La información se obtuvo de 60 estaciones durante mayo y junio de 1996. En cada estación se pescó durante 30 minutos y se capturaron en promedio 100 organismos por cuadrante de 0.5º de lado. La hipótesis que se planteó fue que si la temperatura del agua es un factor que incide en el desplazamiento del calamar, entonces podemos inferir q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 4 publications
0
9
2
9
Order By: Relevance
“…The high concentration of squids in this area has not been explained yet, but the influence of the sea temperature has been discarded as a key factor since Nevárez-Martínez et al (2000) demonstrated that there is not a relationship of the abundance and squid distribution with the water temperature, from the surface to 70-m deep. This contrasts with the explanation given by Brito-Castillo et al (2000), for the analysis of data from the same research survey. Brito-Castillo et al (2000) infer that the catch of the giant squid is successful within an optimum water temperature range (OWTR), this from a hypothesis that supposes that the water temperature is a factor that affects squid's displacement, in such a way that catches can be related to the average temperature in the fishing zones.…”
Section: Introductioncontrasting
confidence: 49%
See 4 more Smart Citations
“…The high concentration of squids in this area has not been explained yet, but the influence of the sea temperature has been discarded as a key factor since Nevárez-Martínez et al (2000) demonstrated that there is not a relationship of the abundance and squid distribution with the water temperature, from the surface to 70-m deep. This contrasts with the explanation given by Brito-Castillo et al (2000), for the analysis of data from the same research survey. Brito-Castillo et al (2000) infer that the catch of the giant squid is successful within an optimum water temperature range (OWTR), this from a hypothesis that supposes that the water temperature is a factor that affects squid's displacement, in such a way that catches can be related to the average temperature in the fishing zones.…”
Section: Introductioncontrasting
confidence: 49%
“…This contrasts with the explanation given by Brito-Castillo et al (2000), for the analysis of data from the same research survey. Brito-Castillo et al (2000) infer that the catch of the giant squid is successful within an optimum water temperature range (OWTR), this from a hypothesis that supposes that the water temperature is a factor that affects squid's displacement, in such a way that catches can be related to the average temperature in the fishing zones. However, to understand the success in the catch of giant squid in the Gulf of California, the adequate index for the fishery has to be estimated.…”
Section: Introductioncontrasting
confidence: 49%
See 3 more Smart Citations